1974
DOI: 10.1037/h0081862
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensionality of internal versus external control: Addition of a third dimension and non-distinction of self versus others.

Abstract: Two separate dimensions called Fatalism and Social System Control (ssc) have been identified in recent research on I-E. The present studies were undertaken to examine whether subdimensions or other separate factors besides these two existed in I-E. It was found that contrary to previous interpretations Ss do not distinguish control of self from control of others within these two dimensions. Rather, the factor analytic data supported the interpretation that Fatalism and ssc differ only in terms of their "source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
0
2

Year Published

1985
1985
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(87 citation statements)
references
References 16 publications
6
79
0
2
Order By: Relevance
“…Employing Reid and Ware's (1974) multidimensional I-E Scale, Harding and Lachenmeyer (1986) reported support for this model by showing that 30-year-old anorexics were external. However, Strober (1982), who used Nowicki and Strickland's (1973) I-E Scale, found that adolescent anorexics demonstrated an internal locus of control.…”
mentioning
confidence: 99%
“…Employing Reid and Ware's (1974) multidimensional I-E Scale, Harding and Lachenmeyer (1986) reported support for this model by showing that 30-year-old anorexics were external. However, Strober (1982), who used Nowicki and Strickland's (1973) I-E Scale, found that adolescent anorexics demonstrated an internal locus of control.…”
mentioning
confidence: 99%
“…A 32-item multidimensional version of Rotter's scale of internal versus external locus of control (Reid & Ware, 1974) Couple Relationship: Study 2 Dyadic Adjustment Scale (DAS). This 32-item scale assesses four basic components of marital adjustment: satisfaction, cohesion, consensus, and affectional expression.…”
Section: Appendixmentioning
confidence: 99%
“…She also found evidence for a possible third dimension: control by oneself. This was confirmed by Reid & Ware (1974) who measured the locus of control of 167 university students and used factor analysis to reveal the same three dimensions. In the light of this research, Coovert & Goldstein (1980) carried out a second experiment with 65 subjects.…”
Section: Introductionmentioning
confidence: 62%